A composite positive electrode material and preparation method thereof

By using a composite positive electrode material with lithium iron phosphate as the core and graphene film as the coating layer in LiFePO4, and preparing it by hydrothermal reaction and sintering technology, the problem of poor effect of graphene conductive additives in the prior art was solved, and the capacitance and cycling performance of lithium-ion batteries were significantly improved.

CN119230803BActive Publication Date: 2025-03-04HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411722645.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing use of graphene as a conductive additive to prepare LiFePO4 positive electrode material is poor, resulting in less obvious improvement in battery performance.

Method used

The composite positive electrode material with lithium iron phosphate as the core and graphene film as the coating layer was prepared by end amino hyperbranched polymer modified graphene oxide, hydroxyethyl phosphonic acid, lithium source, iron source and other raw materials, and hydrothermal reaction and sintering processes.

Benefits of technology

By forming a tight bond between the graphene film and lithium iron phosphate, the capacitance and high-ratio cycling performance of the lithium-ion battery are significantly improved, and the self-aggregation problem of graphene is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230803B_ABST
    Figure CN119230803B_ABST
Patent Text Reader

Abstract

The invention discloses a composite positive electrode material and a preparation method thereof, belonging to the technical field of lithium battery positive electrode materials, wherein the composite positive electrode material is a graphene oxide modified by a terminal amino hyperbranched polymer, hydroxyethylidene diphosphonic acid, a lithium source, and an iron source as raw materials, a precursor is prepared by hydrothermal reaction, and then obtained by sintering. The present invention uses the graphene oxide modified by the terminal amino hyperbranched polymer as a substrate, and under the catalytic action of 4-dimethylaminopyridine, hydroxyethylidene diphosphonic acid is grafted by chemical bonds, and then the chelation of hydroxyethylidene diphosphonic acid is utilized to form a graphene film / lithium iron phosphate composite positive electrode material with in-situ synthesis effect, nano effect, and core / shell structure characteristics, the graphene film and lithium iron phosphate are tightly combined, and during the battery charge and discharge process, the lithium iron phosphate is not easy to fall off, which greatly improves the electric capacity and high rate cycle performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery positive electrode materials, and in particular relates to a composite positive electrode material and a preparation method thereof. Background Art

[0002] Currently, the commonly used positive electrode materials for lithium-ion batteries include lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt oxide, lithium iron phosphate and lithium nickel cobalt manganese oxide ternary materials. Among them, lithium iron phosphate is widely used in lithium-ion battery materials due to its good cycle performance and safety. Its theoretical discharge capacity is 170mAh / g, but its electronic conductivity and ionic conductivity are very low, so it is urgent to find a way to improve the performance of lithium-ion battery positive electrode materials.

[0003] Graphene is a two-dimensional crystal composed of sp2 hybridized carbon atoms, with good electrical conductivity and large specific surface area. The excellent electrical properties of graphene make it suitable as a conductive additive. The patent application with publication number CN101752561A improves battery performance by mixing graphene with LiFePO4 particles to obtain a composite. However, direct mixing makes the combination of LiFePO4 particles and graphene weak, and cannot avoid the agglomeration of graphene itself, resulting in the final improvement effect is not obvious. Summary of the invention

[0004] The object of the present invention is to provide a composite positive electrode material and a preparation method thereof, so as to solve the problem that the existing method of using graphene as a conductive additive to prepare LiFePO4 positive electrode material has poor effect.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A composite positive electrode material is a positive electrode material with lithium iron phosphate as the core and a graphene film as the coating layer. Specifically, the composite positive electrode material is prepared by using amino-terminated hyperbranched polymer modified graphene oxide, hydroxyethylidene diphosphonic acid, a lithium source and an iron source as raw materials, using a hydrothermal reaction to prepare a precursor, and then sintering the precursor to obtain the composite positive electrode material.

[0007] Furthermore, the amino-terminated hyperbranched polymer modified graphene oxide comprises the following steps:

[0008] EDC, NHS, amino-terminated hyperbranched polymer and NaOH were added to the graphene oxide aqueous dispersion in sequence, ultrasonically dispersed evenly, stirred for reaction at 60° C. for 24 h, and then centrifuged, washed with water, and freeze-dried to obtain.

[0009] Furthermore, the mass ratio of graphene oxide, EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride), NHS (N-hydroxysuccinimide), amino-terminated hyperbranched polymer and NaOH is 0.1:0.3:0.3:1:0.01, and the mass fraction of graphene oxide in the graphene oxide aqueous dispersion is 0.1%.

[0010] Under the action of EDC and NHS, the carboxyl groups on the surface of graphene oxide react with the amino groups of the amino-terminated hyperbranched polymer to undergo an amide reaction. Under alkaline conditions, the epoxy groups on the surface of graphene oxide react with the amino groups of the amino-terminated hyperbranched polymer to undergo a ring-opening reaction, so that the amino-terminated hyperbranched polymer is connected to the surface of graphene oxide through chemical bonds, thereby obtaining amino-terminated hyperbranched polymer-modified graphene oxide.

[0011] Furthermore, the amino-terminated hyperbranched polymer is at least one of hyperbranched polyamide, hyperbranched polyamide-amine, hyperbranched polyimide, hyperbranched polyetheramine and hyperbranched polyethyleneimine, and has a weight average molecular weight of 5000-10000, preferably hyperbranched polyamide-amine.

[0012] Furthermore, the number of layers of the graphene oxide is at least one of 1-2 layers, 3-5 layers and 6-10 layers.

[0013] Furthermore, the lithium source is at least one of lithium hydroxide, lithium acetate, lithium carbonate, lithium nitrate and lithium oxalate.

[0014] Furthermore, the iron source is a water-soluble ferrous compound, preferably at least one of ferrous sulfate heptahydrate, ferrous carbonate, ferrous chloride, ferrous hydroxide, ferrous nitrate, ferrous oxalate and ferrous citrate.

[0015] The method for preparing the composite positive electrode material comprises the following steps:

[0016] S1, dissolving an iron source and a lithium source in deionized water to obtain a solution A for standby use; adding hydroxyethylidene diphosphonic acid, amino-terminated hyperbranched polymer-modified graphene oxide and 4-dimethylaminopyridine into deionized water, ultrasonically dispersing for 10-20 min, stirring and reacting at 70° C. for 12 h, cooling to room temperature and transferring to a hydrothermal reactor, then adding solution A to the hydrothermal reactor, stirring evenly under a protective atmosphere, and then performing a hydrothermal reaction at 180-220° C. for 5-8 h. After the reaction is completed, separating, washing and drying to obtain a precursor;

[0017] S2. Sintering the precursor under a protective atmosphere to obtain the composite positive electrode material.

[0018] Furthermore, the molar ratio of Li:Fe:P in the lithium source, iron source and hydroxyethylidene diphosphonic acid in S1 is 1-3:1:1.

[0019] Furthermore, the sum of the mass percentages of the iron source and the lithium source in solution A in S1 is 10-20%.

[0020] Furthermore, the amount of the amino-terminated hyperbranched polymer modified graphene oxide in S1 is 8-12% of the mass of hydroxyethylidene diphosphonic acid, and the amount of 4-dimethylaminopyridine is 1% of the mass of hydroxyethylidene diphosphonic acid.

[0021] Furthermore, in S2, the sintering temperature is 650-700°C, the sintering time is 5-10h, and the heating rate during the sintering process is 2-10°C / min.

[0022] Furthermore, the protective atmosphere in S1 and S2 is one of nitrogen, helium and argon.

[0023] Beneficial effects of the present invention:

[0024] The invention uses amino-terminated hyperbranched polymer modified graphene oxide as a substrate, grafts hydroxyethylidene diphosphonic acid through chemical bonds under the catalytic action of 4-dimethylaminopyridine, and then utilizes the chelation effect of hydroxyethylidene diphosphonic acid to form a graphene film / lithium iron phosphate composite positive electrode material with in-situ synthesis effect, nano effect and core / shell structure characteristics. The graphene film and lithium iron phosphate are tightly combined, and the lithium iron phosphate is not easy to fall off during the battery charging and discharging process, thereby greatly improving the capacity and high-rate cycle performance of the lithium ion battery.

[0025] The present invention uses amino-terminated hyperbranched polymer modified graphene oxide as a substrate. Compared with directly using graphene oxide, the self-aggregation of graphene oxide in the reaction process is hindered, so that the graphene oxide can fully exert its conductive effect. In addition, the hyperbranched polymer molecules contain a large number of tiny cavities. After high-temperature calcination, a carbon layer with a porous structure is formed, which enriches the internal gaps of the composite positive electrode material and provides more channels for electron transport and ion diffusion.

[0026] The present invention limits the proportion of the amino-terminated hyperbranched polymer modified graphene oxide to the mass of hydroxyethylidene diphosphonic acid. When the proportion is too low, the graphene cannot form an effective conductive path with the lithium iron phosphate and cannot effectively improve the ion diffusion effect. When the proportion is too high, the unique steric hindrance effect of the graphene will hinder the diffusion of lithium ions, thereby affecting the electrochemical performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described below in conjunction with the accompanying drawings.

[0028] Figure 1 This is a TEM image of the composite positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The hyperbranched polyamidoamine (dendritic PAMAM) in this application was purchased from Weihai Chenyuan Molecular New Materials Co., Ltd., model CYD-130A.

[0031] Preparation Example 1

[0032] The preparation of amino-terminated hyperbranched polymer modified graphene oxide comprises the following steps:

[0033] Graphene oxide (1-2 layers) was ultrasonically dispersed in deionized water at 20°C to obtain a 0.1wt% graphene oxide aqueous dispersion. 3g EDC, 3g NHS, 10g hyperbranched polyamide-amine and 0.1g NaOH were added to 1000g of the 0.1wt% graphene oxide aqueous dispersion in sequence, and ultrasonically dispersed uniformly. The mixture was stirred and reacted at 60°C for 24h, and then centrifuged, washed with water, and freeze-dried to obtain the result.

[0034] Preparation Example 2

[0035] The preparation of amino-terminated hyperbranched polymer modified graphene oxide comprises the following steps:

[0036] Graphene oxide (6-10 layers) was ultrasonically dispersed in deionized water at 45° C. to obtain a 0.1 wt% graphene oxide aqueous dispersion. 3 g EDC, 3 g NHS, 10 g hyperbranched polyamide-amine and 0.1 g NaOH were added to 1000 g of the 0.1 wt% graphene oxide aqueous dispersion in sequence, and ultrasonically dispersed uniformly. The mixture was stirred and reacted at 60° C. for 24 h, and then centrifuged, washed with water and freeze-dried to obtain the result.

[0037] Example 1

[0038] A method for preparing a composite positive electrode material comprises the following steps:

[0039] S1, 278.01g of ferrous sulfate heptahydrate and 23.95g of lithium hydroxide were dissolved in 1.5L of deionized water to obtain solution A for standby use; 103.15g of hydroxyethylidene diphosphonic acid, 8.2g of the amino-terminated hyperbranched polymer modified graphene oxide of Preparation Example 1 and 1g of 4-dimethylaminopyridine were added to 1L of deionized water, ultrasonically dispersed for 10min, stirred at 70°C for 12h, cooled to room temperature and transferred to a hydrothermal reactor, then solution A was added to the hydrothermal reactor, stirred evenly under a nitrogen atmosphere, and then a hydrothermal reaction was carried out at 180°C for 8h. After the reaction was completed, a solid product was separated, washed with deionized water and dried to obtain a precursor;

[0040] S2. Sintering the precursor in a protective atmosphere at a sintering temperature of 650° C. for 10 h and a heating rate of 2° C. / min to obtain the composite positive electrode material.

[0041] The microscopic morphology of the composite positive electrode material obtained in this example was observed, and the results were as follows: Figure 1 As shown by Figure 1 It can be seen that the composite positive electrode material is a graphene film / lithium iron phosphate composite positive electrode material with nano effect and core / shell structure characteristics.

[0042] Example 2

[0043] A method for preparing a composite positive electrode material comprises the following steps:

[0044] S1, 278.01g of ferrous sulfate heptahydrate and 47.9g of lithium hydroxide were dissolved in 1.7L of deionized water to obtain solution A for standby use; 103.15g of hydroxyethylidene diphosphonic acid, 10.0g of the amino-terminated hyperbranched polymer modified graphene oxide of Preparation Example 1 and 1g of 4-dimethylaminopyridine were added to 1L of deionized water, ultrasonically dispersed for 15min, stirred at 70°C for 12h, cooled to room temperature and transferred to a hydrothermal reactor, then solution A was added to the hydrothermal reactor, stirred evenly under a helium atmosphere, and then a hydrothermal reaction was carried out at 200°C for 6.5h. After the reaction was completed, a solid product was separated, washed with deionized water and dried to obtain a precursor;

[0045] S2. Sintering the precursor in a helium atmosphere at a sintering temperature of 680° C. for 8 h and a heating rate of 5° C. / min to obtain the composite positive electrode material.

[0046] Example 3

[0047] A method for preparing a composite positive electrode material comprises the following steps:

[0048] S1, 278.01g of ferrous sulfate heptahydrate and 71.85g of lithium hydroxide were dissolved in 2L of deionized water to obtain solution A for standby use; 103.15g of hydroxyethylidene diphosphonic acid, 12.4g of the amino-terminated hyperbranched polymer modified graphene oxide of Preparation Example 2 and 1g of 4-dimethylaminopyridine were added to 1L of deionized water, ultrasonically dispersed for 20min, stirred at 70°C for 12h, cooled to room temperature and transferred to a hydrothermal reactor, then solution A was added to the hydrothermal reactor, stirred evenly under an argon atmosphere, and then a hydrothermal reaction was carried out at 220°C for 5h. After the reaction was completed, a solid product was separated, washed with deionized water and dried to obtain a precursor;

[0049] S2. Sintering the precursor in an argon atmosphere at a sintering temperature of 700° C. for 5 h and a heating rate of 10° C. / min to obtain the composite positive electrode material.

[0050] Comparative Example 1

[0051] A method for preparing a composite positive electrode material. Compared with Example 1, the "amino-terminated hyperbranched polymer modified graphene oxide" in Example 1 is replaced by "graphene oxide (1-2 layers)", and the remaining raw materials, parameters and preparation process are the same as Example 1.

[0052] Comparative Example 2

[0053] A method for preparing a composite positive electrode material comprises the following steps:

[0054] S1, 278.01g of ferrous sulfate heptahydrate and 71.85g of lithium hydroxide were dissolved in 2L of deionized water to obtain solution A for standby use; 103.15g of hydroxyethylidene diphosphonic acid and 12.4g of the amino-terminated hyperbranched polymer modified graphene oxide in Preparation Example 2 were added to 1L of deionized water, ultrasonically dispersed for 20min, cooled to room temperature and transferred to a hydrothermal reactor, then solution A was added to the hydrothermal reactor, stirred evenly under an argon atmosphere, and then a hydrothermal reaction was carried out at 220°C for 5h. After the reaction was completed, a solid product was separated, washed with deionized water and dried to obtain a precursor;

[0055] S2. Sintering the precursor in an argon atmosphere at a sintering temperature of 700° C. for 5 h and a heating rate of 10° C. / min to obtain the composite positive electrode material.

[0056] Comparative Example 3

[0057] A method for preparing a composite positive electrode material. Compared with Example 1, the "8.2g of Preparation Example 1 terminal amino hyperbranched polymer modified graphene oxide" in Example 1 is replaced by "7.2g of Preparation Example 1 terminal amino hyperbranched polymer modified graphene oxide", and the remaining raw materials, parameters and preparation process are the same as Example 1.

[0058] Comparative Example 4

[0059] A method for preparing a composite positive electrode material. Compared with Example 3, the "12.4g of Preparation Example 2 terminal amino hyperbranched polymer modified graphene oxide" in Example 3 is replaced by "13.4g of Preparation Example 2 terminal amino hyperbranched polymer modified graphene oxide", and the remaining raw materials, parameters and preparation process are the same as Example 3.

[0060] The composite positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-4 were respectively used as active materials, 85wt% of active materials, 10wt% of acetylene black and 5wt% of binder polyvinylidene fluoride were ground and mixed, then N-methylpyrrolidone was added and stirred evenly, coated on aluminum foil to make a positive electrode sheet, and vacuum dried at 110°C in a vacuum drying oven for 8h. A metal lithium sheet was used as a negative electrode, a polypropylene microporous membrane (Celgard 2400) was used as a diaphragm, and a 1mol / L LiPF6 mixed solution was used as an electrolyte. The solvent in the electrolyte was ethylene carbonate (EC) and diethyl carbonate (DEC), and the volume ratio of EC to DMC was 1:1. A button battery was assembled in an argon-filled glove box, and a charge and discharge cycle test was performed using a battery programmable tester. The voltage range was 2.5-4.1V. The test results are shown in Table 1:

[0061]

[0062] It can be seen from the data recorded in Table 1 that, compared with Comparative Examples 1-4, the composite positive electrode material obtained in Examples 1-3 has higher discharge specific capacity and high rate cycle performance, and the specific capacity retention rate after 1000 cycles at 2C rate is greater than 97%. Specifically, it can be seen from the test results of Example 1 and Comparative Example 1 that directly using graphene oxide as an additive, due to the self-aggregation problem, the electrochemical performance of the obtained positive electrode material is significantly inferior to that of Example 1. It can be seen from the test results of Example 1 and Comparative Example 2 that in the present application, the amino-terminated hyperbranched polymer-modified graphene oxide and hydroxyethylidene diphosphonic acid are heat-treated in the presence of 4-dimethylaminopyridine. The obtained positive electrode material has better performance. It can be seen from the test results of Example 1 and Comparative Example 3, Example 3 and Comparative Example 4 that the proportion of amino-terminated hyperbranched polymer-modified graphene oxide to the mass of hydroxyethylidene diphosphonic acid should be strictly controlled. If the proportion is too low or too high, the electrochemical performance of the composite positive electrode material will decrease.

[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite positive electrode material, characterized in that: The composite positive electrode material is a positive electrode material with lithium iron phosphate as the core and graphene film as the coating layer. It uses amino-terminated hyperbranched polymer modified graphene oxide, hydroxyethylidene diphosphonic acid, lithium source, and iron source as raw materials. Under the catalytic action of 4-dimethylaminopyridine, a hydrothermal reaction is used to prepare a precursor, and then the precursor is sintered to obtain the composite positive electrode material. The molar ratio of Li:Fe:P in the lithium source, the iron source and the hydroxyethylidene diphosphonic acid is 1-3:1:1; The amount of the amino-terminated hyperbranched polymer modified graphene oxide is 8-12% of the mass of hydroxyethylidene diphosphonic acid.

2. A composite positive electrode material according to claim 1, characterized in that: The amino-terminated hyperbranched polymer modified graphene oxide comprises the following steps: EDC, NHS, amino-terminated hyperbranched polymer and NaOH were added to the graphene oxide aqueous dispersion in sequence, ultrasonically dispersed evenly, stirred for reaction at 60° C. for 24 h, and then centrifuged, washed with water, and freeze-dried to obtain.

3. A composite positive electrode material according to claim 2, characterized in that: The mass ratio of graphene oxide, EDC, NHS, amino-terminated hyperbranched polymer and NaOH is 0.1:0.3:0.3:1:0.01, and the mass fraction of graphene oxide in the graphene oxide aqueous dispersion is 0.1%.

4. A composite positive electrode material according to claim 2, characterized in that: The amino-terminated hyperbranched polymer is at least one of hyperbranched polyamide, hyperbranched polyamide-amine, hyperbranched polyimide, hyperbranched polyetheramine and hyperbranched polyethyleneimine, and has a weight average molecular weight of 5000-10000.

5. A composite positive electrode material according to claim 2, characterized in that: The number of layers of the graphene oxide is at least one of 1-2 layers, 3-5 layers and 6-10 layers.

6. A method for preparing a composite positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, dissolving an iron source and a lithium source in deionized water to obtain a solution A for standby use; adding hydroxyethylidene diphosphonic acid, amino-terminated hyperbranched polymer-modified graphene oxide and 4-dimethylaminopyridine into deionized water, ultrasonically dispersing for 10-20 min, stirring and reacting at 70° C. for 12 h, cooling to room temperature and transferring to a hydrothermal reactor, then adding solution A to the hydrothermal reactor, stirring evenly under a protective atmosphere, and then performing a hydrothermal reaction at 180-220° C. for 5-8 h. After the reaction is completed, separating, washing and drying to obtain a precursor; S2. Sintering the precursor under a protective atmosphere to obtain the composite positive electrode material.

7. The method for preparing a composite positive electrode material according to claim 6, characterized in that: The amount of 4-dimethylaminopyridine in S1 is 1% of the mass of hydroxyethylidene diphosphonic acid.

8. The method for preparing a composite positive electrode material according to claim 6, characterized in that The sintering temperature in S2 is 650-700°C, the sintering time is 5-10h, and the heating rate during the sintering process is 2-10°C / min.

9. The method for preparing a composite positive electrode material according to claim 6, characterized in that: The protective atmosphere in S1 and S2 is one of nitrogen, helium and argon.

Citation Information

Patent Citations

  • Graphite alkene iron lithium phosphate positive active material, preparing method thereof, and lithium ion twice battery based on the graphite alkene modified iron lithium phosphate positive active material

    CN101752561A

  • Method for modifying epoxy resin through amino-terminated hyperbranched polymer-grafted graphene oxide

    CN102504147A

  • Filling type flexible strain sensing material and preparation method thereof

    CN113930037A